CASE REPORT SYPHILIS WITH PALMOPLANTAR PSORIASIS MANIFESTATIONS - Sherlina Lesmana, Rizka Cindy; Fitriana, Ilma; Ahmed, Rafdi; Wijaya, Diana (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
In the period from januari to march 2021, 2.976 cases of early syphilis were reported and 892 cases of advanced syphilis in Indonesia.4 Syphilis is a sexually transmitted infection caused by Treponema pallidum. spread by direct contact with lesions or vertically during pregnancy. The typical manifestation of syphilis is a painless papule or ulcer with a clean base. divided into 4 phases namely primary, secondary, latent and tertiary. The diagnosis of syphilis is based on serology, namely non-treponemal and treponemal tests. For the treatment of syphilis, Benzathine Penicillin G can be given in the amount of 2.4 million intramuscular units in a single dose or alternative therapy can be given 2 x 100 mg doxycycline for 14 days for primary and secondary stages, 28 days for latent stages.1